Marketing Communication Strategy of Online Shop to take advantage of Instagram Application (Case Study on Online Shop @cutrizkyhijab1) - Laila Rohani; M.Yoserizal Saragih; Anang Anas Azhar; Anita Wulanie Fitri (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This study aims to find out online shop marketing communications @cutrizkyhijab1 on instagram and to find out the advantages and disadvantages of online shop@cutrizkyhijab1on marketing through Instagram media. The theory used in this study is the theory of social media, Instagram, marketing communication, and the Marketing Mix. The subjects of this research are Owners and 10 permanent consumers cutrizkyhijab1 listen research time from April to August. The method used in this research is the Qualitative Method with In-depth Interview (in-depth interview). Technical analysis used is descriptive qualitative analysis. The results of this study indicate that the marketing communication strategy carried out through Instagram media is used by online shop owner @cutrizkyhijab1through promotions on the Instagram application. Of the various supporting features on Instagram, the features that are most often used are the Instagram photo upload feature and Story Highlights. The advantages of online shop@cutrizkyhijab1Compared to other online shops, it lies in conveying messages to consumers by using the features available on Instagram, prices and up to date products for each product variation. Disadvantages of online shop@cutrizkyhijab1 in the form of competition between other online shops, thus making the owner @cutrizkyhijab1 must be diligent to post photos or videos so that their products can be seen by consumers.